Professional discretion and length of work experience: what findings from focus groups with care managers in elder care suggest. Issue 2 (3rd April 2018) - Olaison, Anna; Torres, Sandra; Forssell, Emilia
ABSTRACT: Research has explored how care managers in elder care – who often function as 'street-level bureaucrats' – regard professional discretion. The way in which length of work experience affects care managers' use of professional discretion remains, however, unexplored. This article present findings from 12 focus groups with 60 care managers. By bringing attention to how care managers experience the needs assessment process, this article sheds light on how these 'street-level bureaucrats' struggle when they try to balance their clients' needs against institutional frameworks and local guidelines. Length of work experience seems to play a role in how care managers claim to use professional discretion. Experienced care managers describe how they deviate from the guidelines at times in order to create an increased scope of action in their decision-making process. Those with less time in the profession describe greater difficulties in this respect. Findings suggest that research should explore if length of work experience plays a role in the actual way in which care managers assess needs and make decisions. As such, they contribute to our understanding of how needs assessment processes are navigated by professionals while also pointing towards the nature of professional discretion in gerontological social work.